Did Demonetization Affect Indian Stock Market? - Sohail Raza; Shahzad Munir (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2022)
This study explores the impact of "2016 demonetization" on the stock market inIndia. The policy declared 86% of cash in circulation in the form of Indian rupees(INR) 500 & 1000 notes as an illegal tender effective from midnight of November8, 2016. However, India’s government progressively released new 500 and 2000INR notes over the next few months. Following the demonetization announcement, stock prices of cash-sensitive industries like consumer goods and financial services dropped rapidly, reflecting a significant reduction in demand. This study focuses on the short-term effects of demonetization on the stock prices of 100 publicly listed firms using their daily stock data. We use estimating windows within 60 days of the announcement and then capture the short-term effects of demonetization by employing the Ordinary Least Square (OLS), the Fixed Effect (FE), and the Random Effect (RE) methods. Estimation results demonstrate that demonetization effectively decreases stock prices. https://doi.org/10.21632/irjbs.15.1.1-15